Effects of the carrier agents addition on the lyophilized red pitaya pulp powder (H. polyrhizus) (Research, Society and Development, 2020)
The aim of this study was to evaluate the influence of maltodextrin, gum arabic and dextrin on the lyophilized red pita pulp powder. The pitaya pulp was characterized by moisture content, water activity, pH, total titratable acidity, total soluble solids, ascorbic acid, color, betalains and phenolic compounds content. The carrier agents influence on the powder was evaluated through a simplex-centroid mixture design and the powder hygroscopicity, humidity, Carr index (CI) and the Hausner ratio (RH) were determined. The pitaya pulp showed a high moisture content, good ascorbic acid and total phenolic compounds content, low acidity and soluble solids. The powder hygroscopicity ranged from 10.37 to 6.55% and powder moisture content ranged from 3.17 to 4.78%. The samples Carr index ranged from 22.61 to 43.00% and Housner ratio from 1.29 to 1.75. Increasing the concentration of maltodextrin and decreasing dextrin and gum arabic in the mixture reduced the values of IC and RH. The dextrin concentration increase in the mixture contributed to the powders moisture reduction, and gum arabic increase contributed to the powders hygroscopicity increase. Among the carrier agents used, maltodextrin was the one that most contributed to the better fluidity of pitaia pulp powder.